HPBR:host packet behavior ranking model used in worm detection - XIAO Feng-tao1; HU Hua-ping1; LIU Bo1; CHEN Xin1 (Tongxin xuebao)
Based on defining the access behavior model of a user,a model named HPBR（host packet behavior ranking） was presented,which ranked the network packets from and to the host.Hierarchical accumulative ranking procedure,performance analysis and optimization procedure in HPBR were described.At last,an example on using HPBR is intro-duced.